2001
DOI: 10.1002/fam.771
|View full text |Cite
|
Sign up to set email alerts
|

Screening tests for fire safety of composites for marine applications

Abstract: Demands for reduced maintenance, reduced manning and reduced cost are resulting in the need for new and alternative materials for introduction in the fleet. The new materials in many cases tend to be non-metallic and organic (combustible) materials. In order to maintain a minimum level of fire safety, the US Navy has set performance requirements for new materials in many applications. These include the use of composite materials in ships and submarines. Performance requirements for composites, in most cases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The only measurement that increased in value with increasing S-2 glass content was the time to ignition, which went to longer times (delayed ignition) as the fiberglass content was increased in the epoxy composites. In general, these trends fit with those observed elsewhere in that as fiber content is increased, heat release decreases [24][25][26][27][28].…”
Section: Bisphenol F Epoxy Composites: Effects Of S-2 Glass Fiber Loasupporting
confidence: 88%
“…The only measurement that increased in value with increasing S-2 glass content was the time to ignition, which went to longer times (delayed ignition) as the fiberglass content was increased in the epoxy composites. In general, these trends fit with those observed elsewhere in that as fiber content is increased, heat release decreases [24][25][26][27][28].…”
Section: Bisphenol F Epoxy Composites: Effects Of S-2 Glass Fiber Loasupporting
confidence: 88%
“…Thermogravimetric Analysis TGA, Differential Thermal Analysis DTA, or Differential Scanning Analysis DSC) [3][4][5][6][7] but also in small ones (i.e. ISO 5660 cone calorimeter) [8][9][10][11][12][13][14][15][16][17][18][19]. The last draws a wide attention in recent studies because of the better assessment of material behaviors in real fire scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The last draws a wide attention in recent studies because of the better assessment of material behaviors in real fire scenarios. Several reaction-to-fire properties of fiber-reinforced epoxy resin composites have been measured such as: time-to-ignition, heat release rate (HRR), amount and rate of mass loss, density and specific extinction area of smoke, gaseous emissions as well as limit oxygen index (LOI) [8][9][10][11][12][13][14][15][16][17][18][19]. It is found that different parameters as external heat flux, composite properties (nature of fiber, fiber content and fiber arrangement within composite, sample thickness) and fire environment condition, can have an influence on the thermal properties of composite.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the higher fire risk with naval vessels, many navies do not have clearly defined fire safety regulations. Some navies are considering adopting the IMO code for high-speed craft to their surface vessels, while other navies -most notably the United States Navy (USN)have established their own regulations to meet the unique operating conditions of warships and submarines [4,[16][17][18][19].…”
Section: Fire Safety Regulations For Ships and Submarinesmentioning
confidence: 99%
“…The USN has established two guiding principles for the use of composite materials in their vessels: (i) the material itself must not be the fire source and (ii) the flammability resistance of the material must be sufficient to allow the crew to respond to the primary fire source [4,[17][18][19][20]. Currently there is no fire safety standard applied to US naval ships, although several criteria have been set to reduce the hazard.…”
Section: Fire Safety Regulations For Ships and Submarinesmentioning
confidence: 99%